2020
DOI: 10.1186/s13019-020-01290-0
|View full text |Cite
|
Sign up to set email alerts
|

Is the flap reinforcement of the bronchial stump really necessary to prevent bronchial fistula?

Abstract: Background/aim The development of bronchopleural fistula (BPF) remains the most severe complication of lung resection, especially after pneumonectomy. Studies provide controversial reports regarding the benefits of flap reinforcement of the bronchial stump (FRBS) in preventing BPF’s occurrence. Methods This is a retrospective cohort study of 558 patients that underwent lung resection in a 12-year period (from 2007 to 2018). Ninety patients (16.1%) underwent pneumonectomy. Patient follow-up period varied from… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0
1

Year Published

2022
2022
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 16 publications
0
3
0
1
Order By: Relevance
“…The literature describes the advantages of several types of autologous tissue buttressing, such as with IMF (28), pleura (27), pericardial fat pad (13,29), or diaphragm (28). A recent study by Caushi et al reported no significant differences between buttressed and non-buttressed bronchial stumps in the occurrence of BPF (30). Some studies consider IMF as a durable and blood supplyadequate material for bronchial buttressing (27,28).…”
Section: Discussionmentioning
confidence: 99%
“…The literature describes the advantages of several types of autologous tissue buttressing, such as with IMF (28), pleura (27), pericardial fat pad (13,29), or diaphragm (28). A recent study by Caushi et al reported no significant differences between buttressed and non-buttressed bronchial stumps in the occurrence of BPF (30). Some studies consider IMF as a durable and blood supplyadequate material for bronchial buttressing (27,28).…”
Section: Discussionmentioning
confidence: 99%
“…In a retrospective study, Taghavi et al, found 93 patients who underwent pneumonectomy for primary lung cancer, identified no BPF during follow up after using a pedicled pericardial flap for bronchial stump coverage [41]. A pericardial fat pad is harvested from the anterolateral pericardium, pedicled at its cranial part, avoiding inclusion or injury to the phrenic nerve [9,42].…”
Section: Pericardial Fat Padmentioning
confidence: 99%
“…Наиболее распространенной причиной их появления является несостоятельность культи бронха после операций на легких [1,2]. В последние десятилетия совершенствование хирургической техники, антибиотикотерапия, улучшение послеоперационного наблюдения привели к снижению частоты развития несостоятельности анастомозов культи бронха с 28 до 3-4% [3,4]. По данным нашего центра, в послеоперационном периоде свищи развиваются в 2,4% случаев.…”
Section: Introductionunclassified